A drug utilization study to evaluate effectiveness of risk minimization measures for trimetazidine in France, Hungary, Romania and Spain. (18th January 2019) - Ehlken, Birgit; Toussi, Massoud; Samad, Abdus; Kaplan, Sigal; Domahidy, Mónika; de Voogd, Hanka; Böhmert, Stella; Silveira Ramos, Rita; Arora, Deepa
Summary: What is known and objective: The approved indication for trimetazidine (TMZ) was restricted to "add‐on therapy for the symptomatic treatment of patients with stable angina pectoris who are inadequately controlled by or intolerant to first‐line antianginal therapies" in 2012 by the Committee for Medicinal Products for Human Use (CHMP). TMZ was no longer indicated for ophthalmology and otolaryngology (ENT) indications. This drug utilization study analysed actual utilization of TMZ before and after the restriction on its indications to evaluate the effectiveness of risk minimization measures (RMM). Methods: This was a multi‐national, cross‐sectional, non‐interventional drug utilization study using European databases: IMS Prescribing Insights (PI) for France and Spain, National Diagnostic Index (NDI) for Romania and National Prescription Audit (NPA) for Hungary. TMZ prescriptions issued by Ear‐Nose‐Throat (ENT) specialists, ophthalmologists, cardiologists and General Physicians (GPs)/others were analysed during the 24‐month period before (reference period) and after RMM implementation (assessment period). Results and discussion: During the assessment period, most of the TMZ prescriptions for ENT and ophthalmology indications (un‐authorized indications) were made by GPs/others followed by ENT specialists, ophthalmologists and cardiologists in most of the countries. The proportion of TMZ prescriptions for ENT or ophthalmological indications after the restrictions on indication was reduced in Hungary (by 0.4%) and Spain (by 11.8%), remained the same in Romania and increased in France (by 3.7%). What is new and conclusion: This study showed that a significant proportion of TMZ prescriptions was off‐label for ENT or ophthalmological indications following the RMM implementation. More effective RMM strategies are required to reduce off‐label prescriptions of TMZ. Abstract : The present study analysed actual utilization of TMZ before and after the restriction on its indications to evaluate effectiveness of risk minimization measures (RMM). TMZ prescriptions were analysed during the 24‐month period before (reference period) and after RMM implementation (assessment period). The proportion of TMZ prescriptions for ENT or ophthalmological indications after the restrictions on indication was reduced in Hungary (by 0.4%) and Spain (by 11.8%), remained the same in Romania and increased in France (by 3.7%). This study showed that significant proportion of TMZ prescriptions is prescribed off‐label, and more effective RMM strategies are required to reduce off‐label prescriptions of TMZ.